Ballistic response of hemispherical sandwich shell structure against ogive nosed projectile. (September 2020) - Khaire, N.; Tiwari, G.
Abstract: This study presents the experimental and numerical investigation of the response of hemispherical sandwich shell structure having hexagonal honeycomb core against ogive nosed projectile impact. Aluminum AA-1100 was considered for the front and rear face sheet of 200 and 160 mm diameter whereas AA-3003H19 was used for the honeycomb core of 3.2 mm cell size, 0.05 mm cell wall thickness and 20 mm core thickness. The cylindrical ogive nosed projectile having diameter 19 mm, mass 52.5 g and length 50.8 mm was hit at the crown of the hemispherical sandwich shell structure. The experiments were carried out through a pneumatic gun whereas for numerical simulations, 3D finite element code Abaqus explicit solver was used. The ballistic resistance, failure mechanism and the energy absorption of the sandwich shell structure was investigated thoroughly through experimentation and numerical simulations and found close to each other. Moreover, the parametric study was performed through numerical simulations to study the influence of face sheet thickness (0.7, 1, 1.5 and 2 mm), cell wall thickness (0.03, 0.05, 0.07 and 0.09 mm) and cell size (3.2, 5.0, 7.0 and 9.0 mm) of the honeycomb core on the ballistic response and energy absorption. Against ogive nosed projectile, face sheets failed in radial stretching with petal formation and the core failed in crushing. Also, the face sheet thickness had a dominant effect on the ballistic limit and the energy absorption of the hemispherical sandwich shell structure. Moreover by increasing core stiffness (by using thick cell wall and small cell size) enhance energy absorption capacity of the sandwich structure. Highlights: Impact response of hemispherical sandwich shell was studied for ogival projectile. The face sheet thickness, cell wall thickness and cell size was varied. Face sheets failed in ductile tearing and core in crushing against ogive projectile. Thicker skin and wall thickness showed higher ballistic-limit and energy absorption. Larger cell size decreased the ballistic limit and energy absorption.